New trends in diagnostic and therapeutic procedures in bioterrorism threats - Płusa, Tadeusz (Przewodnik Lekarza/Guide for GPs, 2008)
Nowadays bioterrorism is a focus of interest throughout the world. It is well known that viral and bacterial pathogens may be useful as biological weapons. Haemorrhagic fevers cased by the Ebola and Marburg viruses are very serious diseases leading to shock and death. The inhaled route of bacterial infections caused by anthrax involves a great area of the lung tissue. The number of inhaled pathogens influences the clinical picture, duration and complications of infection.